Juridical Analysis Of The Legal Standing Of Sharia Financial Institutions – Cash Waqf Recipients Of Sharia Banks Post-Establishment Of Indonesian Sharia Bank - Hidayatullah, Hidayatullah; Aini, Muhammad; Nasrullah, Nasrullah (International Journal of Law, Environment, and Natural Resources, 2022)
The selection of Sharia banks in accepting cash waqf is because in general Sharia banking has several advantages being expected for optimizing the operations of the cash waqf. However, since the election of Sharia banks in accepting cash waqf, in general, Sharia banking has several advantages which expected for optimizing the operations of the cash waqf. On the one hand, the merger raises questions regarding the legal standing and system of cash waqf Recipient by the Sharia banks themselves as Sharia Financial Institutions-Cash Waqf Recipient (SFI-CWR), which used to stand separately and are now incorporated in one management. This study aims to provide an overview of the legal standing and management system of the SFI-CWR of the Sharia banks post-establishment of Indonesian Sharia Bank which is a combination of the SFI-CWR of sharia banks. This research is a normative legal research, in which the data are secondary data sourced from laws and regulations, books and other references. Analysis method of the data used is content analysis, which analysing the content of the subject matter studied. From this research activity, it will be found how the status, legal standing and management system of SFI-CWR of Sharia Banks after the establishment of ISB.